Aleksandr Zhizhilenko and the documents falsification problem - V. V. Bezdrabko (Библиосфера)
The author deals with the concept deconstruction of falsifying documents as acts of written proof, evidence. The paper analyzes A. A. Zhizhilenko's views in the context of influencing the German historical-law school and legal science generally. It attempts to prove the importance of the achievements of legal science for document management.